Stalker a novel - Kellerman, Faye. (New York : Avon Books, 2000)
Determined to hide the truth about her being stalked from her overprotective lieutenant father, rookie cop Cynthia Decker is forced to reconsider when things heat up and she realizes their two cases may be related.
Keywords: Decker, Peter (Fictitious character) -- Fiction; Lazarus, Rina (Fictitious character) -- Fiction; Police -- California -- Los Angeles -- Fiction; Stalking victims -- Fiction; Los Angeles (Calif.) -- Fiction; Mystery fiction